2023
DOI: 10.1213/ane.0000000000006355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tulobuterol Patch Versus Placebo on the Occurrence of Respiratory Adverse Events in Children Undergoing Tonsillectomies: A Randomized Controlled Trial

Abstract: BACKGROUND: Perioperative respiratory adverse events are common in children. We aimed to evaluate the effect of the transdermal β-2 agonist, tulobuterol, compared with that of placebo on the incidence of perioperative respiratory adverse events in pediatric patients undergoing tonsillectomy. METHODS: In this triple-blinded (patient, anesthesia provider, and outcome assessor) randomized controlled trial, 188 patients were randomly allocated to receive tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 35 publications
(73 reference statements)
0
4
1
Order By: Relevance
“…9 When aiming to reduce PRAEs in a clinically significant manner, and to change routine clinical practice, the most effective method will be to target the highest-risk patient group, namely those with known reactive airway disease or those with a current or recent upper respiratory tract infection. While somewhat interesting, the current study by Kim et al 1 does not support the use of a more onerous and costly method of delivering a beta agonist compared with the more available, cheaper, and the easier-to-perform method of direct inhalation of albuterol in the immediate perioperative setting. Sometimes, it is better to keep things simple and safe.…”
contrasting
confidence: 61%
See 4 more Smart Citations
“…9 When aiming to reduce PRAEs in a clinically significant manner, and to change routine clinical practice, the most effective method will be to target the highest-risk patient group, namely those with known reactive airway disease or those with a current or recent upper respiratory tract infection. While somewhat interesting, the current study by Kim et al 1 does not support the use of a more onerous and costly method of delivering a beta agonist compared with the more available, cheaper, and the easier-to-perform method of direct inhalation of albuterol in the immediate perioperative setting. Sometimes, it is better to keep things simple and safe.…”
contrasting
confidence: 61%
“…The authors' observation of PRAEs in 42.5% of the control group reinforces the inconsequential nature of the criteria being used to define the outcomes. In the study by Kim et al, 1 and in previous studies investigating the preemptive use of beta agonists, the reduction in PRAEs was observed as a reduction in minor events of coughing and obstruction, while the most critically important adverse events of laryngospasm and bronchospasm were, in contrast to the inhaled route, not different between the treatment and placebo groups when using the patch.…”
mentioning
confidence: 79%
See 3 more Smart Citations